Analisis Disparitas Pendapatan dan Pertumbuhan Ekonomi Kabupaten/Kota di Provinsi Bali - Ni Kadek Sri Wahyuni; Ida Bagus Putu Purbadharmaja (Journal Of Business, Finance, and Economics (JBFE), 2024)
The purpose of this study is to find out the factors that can affect economic growth and income disparity of districts/cities in Bali Province. The data used in this study is secondary data obtained from the Badan Pusat Statistik (BPS) of Bali Province. The method of data collection is a non-participant observation method with a total of 90 observations starting from 2013-2022. The analysis technique used is the path analysis technique. The results of the study show that (1) Directly investment has a positive and insignificant effect, minimum wage has a negative and significant effect, and government expenditure has a positive and significant effect on the economic growth of districts/cities in Bali Province. (2) Directly investment has a positive and insignificant effect, minimum wage has a negative and significant effect, government expenditure and economic growth have a negative and insignificant effect on the income disparity of districts/cities in Bali Province. (3) Indirectly, investment, minimum wage, and government expenditure have no effect on income disparity through economic growth of districts/cities in Bali Province.